Paleomagnetic Recorder in the West Pacific Ferromanganese Crust - Wonnyon Kim; Jung-Keuk Kang; Chan Min Yoo (International Marine Minerals Society, 2017)
Recently high-resolution paleomagnetic age determination of ferromanganese crust in less than millimeter scale has been successfully carried out using a superconducting quantum interference device microscopy magnetometer (SMM). However, it has not been clearly identified how the crust is keeping ancient geomagnetic field records. Here we try to identify magnetic mineralogy of the crust obtained in the Magellan Seamounts, the West Pacific (~20 °N). As a record, age of the crust used in this study is extended to ~10 Ma at ~40 mm depth and ~28 Ma at ~100 mm depth, respectively, based on the combination approach of SMM measurements, Be-isotope and Co-chronology. Thermal demagnetization revealed a Curie temperature of ~560oC, corresponding to (titano)magnetite. Component analysis of isothermal remanent magnetization identified a presence of two types of magnetite. Measurements of first order reverse curve showed a dominance of non-interacting single-domain magnetite, which is one of the intrinsic feature of biogenic magnetite. Although most of the magnetic particles on transmitted electron microscopy are covered by amorphous Fe-Mn minerals, some are observed as a prototype of biogenic magnetite showing a chain of ~10 nm sized magnetite cubes. However, a magnetite signal (i.e., Verway transition at ~ –120 oC) was not detected in low-temperature treatment probably due to surface oxidation of magnetite. Contribution of interacting magnetite of detrital origin is <30% throughout a crust. Interestingly, contribution of detrital magnetite is almost three times higher since ~10 Ma. At this boundary, a growth rate of the crust is double up and flux of other detrital signals, including Al, Mg, Ti and Zr, are also increased.